2011
DOI: 10.1111/j.1467-789x.2010.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of fruit and vegetable intake with adiposity: a systematic review

Abstract: SummaryFruit and vegetable (FV) intake has been proposed to protect against obesity. The purpose of this paper was to assess the FV consumption to adiposity relationship. Twenty-three publications were included. Inclusion criteria: longitudinal or experimental designs; FV intake tested in relation to adiposity; child, adolescent or adult participants; published in English-language peer-reviewed journals. Exclusion criteria: dietary pattern and cross-sectional designs; participants with health concerns. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
304
7
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(341 citation statements)
references
References 49 publications
18
304
7
12
Order By: Relevance
“…Contrary to diets in which manufactured products and high levels of fat and sugar predominate, diets with a more frequent fruit/vegetable intake tend to show lower amounts of simple carbohydrates and fats, which is inversely associated with greater calorie intake, a known component of excess body weight 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to diets in which manufactured products and high levels of fat and sugar predominate, diets with a more frequent fruit/vegetable intake tend to show lower amounts of simple carbohydrates and fats, which is inversely associated with greater calorie intake, a known component of excess body weight 29 .…”
Section: Discussionmentioning
confidence: 99%
“…These efforts include promoting increased consumption of low-energy-density foods such as F&V which, on the basis of high water and fibre content, alongside their low fat content, collectively yield larger bulk and low energy density. Although the positive effects of low-energy-dense food have been demonstrated in adults (8) , the data are somewhat inconsistent, particularly among children (9)(10)(11) . While many factors influence dietary preferences and habits, encouraging children to consume recommended amounts of F&V is often part of programming conducted in schools (12)(13)(14)(15)(16)(17)(18) .…”
mentioning
confidence: 99%
“…In addition, most such evidence is based on self-reported dietary data and, thus, there is limitation in measuring dietary intake as a result of the inaccuracies of self-report. [12][13][14]20,21 Moreover, the relationships between FV intake and adiposity or body weight are documented epidemiologically in adults, but not in children. 12,13 In 2009, Farm to School (F2S) programs were named by the CDC as a strategy to facilitate children's increased access to FV in the school setting.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 It is well demonstrated that FV contain micronutrients important for health, but the primary reason that increased FV intake is suggested within the context of the obesity epidemic is their low energy density and high fiber and water content. [12][13][14] This is based on the presumption that increased intake of FV displaces energy intake from energy-dense foods. [15][16][17] Although the energy density hypothesis is well documented in the laboratory setting, 18,19 there is less evidence that an increase in FV consumption actually displaces consumption of other foods in a free-living situation such that it reduces total energy intake.…”
Section: Introductionmentioning
confidence: 99%